ABUNDANCE OF MARINE DEBRIS ON PADANG AND PARIAMAN BEACHES WEST SUMATRA PROVINCE - Gusmanti, Afni; Nedi, Syahril; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Padang and Pariaman Beaches are regional strategic locations for tourism and have been growing rapidly. However, waste has become a significant concern because of its anthropogenic impact. This study aims to identify and analyze the types of waste abundance on both beaches of these tourist destinations. This research was conducted in August 2022 using a survey method. This study found eight types of waste in the two locations. They comprise plastic, metal, glass, wood, paper, rubber, and cloth fragments. The total fragment on Padang Beach reached 3,392 items/m2, higher during the weekend than before the weekend (1,212 and 1,072 items/m2). Meanwhile, the total fragment on Pariaman Beach reached 2,484 items/m2 and was higher during the weekends than after the weekends (0.956 and 0.74 items/m2). Moreover, there was no significant difference between the two locations (p>0.05). It might relate to the characteristics of the same water quality parameters: the current velocity ranges from 0.3-0.4 m/s (medium current), so it does not have a different effect.